Administrative Violations and Process Disputes in the 2020 Regional Head Election of Bandar Lampung City - Amin Nugrah Santoso; Fitra Arsil (Jurnal Indonesia Sosial Teknologi, 2024)
The 2020 Regional Head Election in Bandar Lampung City is an election process that has been regulated in Law No. 10 of 2016. However, in the stage mechanism there are Systematic and Massive Structured violations according to the findings of the Lampung Provincial Bawaslu based on reports followed up by the Lampung Provincial Bawaslu. The purpose of this study is to find the factors that cause administrative violations in the 2020 Regional Elections in Bandar Lampung City based on Law Number 10 of 2016, explain cases of administrative violations of the Regional Elections related to process disputes and disputes over results, and analyze the process of resolving administrative violations of the Regional Elections against disputes over processes and disputes over results. The research method in writing this thesis is doctrinal law research with a method of collecting data from literature studies to answer problems which then the results are expected to aim at providing solutions or suggestions to overcome problems. Departing from the discussion, disputes over the election administration process and disputes over the results of the Regional Elections are the root of the problem in the 2020 Regional Head Election in Bandar Lampung City. The solution offered is the regulation of the 2020 Regional Elections based on Law Number 10 of 2016 regulating the implementation of the Regional Elections under normal circumstances, meaning that the Covid-19 pandemic has not occurred.